Teoria kosztów transakcyjnych wg O. Williamsona - Pańkowska, Małgorzata (Wydział Prawa i Administracji UAM, 1995)
The paper focuses on outsourcing, one of the theories lying at the grounds of successful cooperation. The issues concerning virtual organisation, H. Simon's theory, the market, hierarchy, specifics of the human assets, site specificity and material resources are briefly discussed. The complexity of the product description, typical and exceptional transactions and certain types of contracts are also considered. It has been pointed out that within one company several outsourcing firms, each of a specific specialisation, may operate. Consequently, a so-called virtual organisation develops. Such an organisation benefits from the fact those different businesses cooperate with one another.
Theory of transaction costs according to Olivier Williamson